2022
DOI: 10.1186/s12888-022-04441-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a pilot, community-led mental illness de-stigmatization theater intervention in rural Uganda

Abstract: Background In rural areas of low- and middle- income countries, mental health care is often unavailable and inaccessible, and stigma is a major barrier to treatment. Destigmatization can increase treatment-seeking attitudes, community support, and acceptance of individuals suffering from mental illness. This study’s primary objective was to evaluate the impact of a community-led, theater-based destigmatization campaign for mental illness conducted in the Busoga region of Eastern Uganda. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The report on the original study suggested that the intervention cohort demonstrated a greater willingness to live, work, interact, and understand those with mental illness [13]. This follow-up study demonstrated that these attitude shifts persist for at least one year and may even become more pronounced after a substantial period of time, suggesting that this model could be used to enact signi cant, long-term change in attitudes amongst rural Ugandans.…”
Section: Meaning Of the Studymentioning
confidence: 74%
See 4 more Smart Citations
“…The report on the original study suggested that the intervention cohort demonstrated a greater willingness to live, work, interact, and understand those with mental illness [13]. This follow-up study demonstrated that these attitude shifts persist for at least one year and may even become more pronounced after a substantial period of time, suggesting that this model could be used to enact signi cant, long-term change in attitudes amongst rural Ugandans.…”
Section: Meaning Of the Studymentioning
confidence: 74%
“…Outcomes were assessed with a 61-item questionnaire that gathered demographic data and included two stigma-focused batteries, the Personal Acceptance Scale (PAS) and the Broad Acceptance Scale (BAS), described in Lee et al [13]. The PAS targets population stigma, and consists of community-in uenced negative attitudes, beliefs, and behaviors towards people with mentally illness.…”
Section: Questionnaire Design and Administrationmentioning
confidence: 99%
See 3 more Smart Citations